PENGARUH LATIHAN THREE CORNER DRILL TERHADAP KELINCAHAN (AGILITY) ATLET PUTRA TAEKWONDO DOJANG TERATAI BRIMOB PEKANBARU - Puspa Juwita Larosa; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Problem in the takwondo athlete of Pekanbaru Dojang Teratai Brimob, show that the agility is still not optimal, it can be seen from the slow pace of athletes in moving when changing the direction of movement in finding positions, even though they are technically at a good level. This is justified by the trainer but in the implementation of the technique movement the athlete looks slow or less agile in carrying out movements that should be done quickly and agile. Because in sports taekwondo agility is needed to avoid the opponent's attack then counterattack quickly. Therefore, to improve the agility of the athletes of the Dojang Teratai Brimob Pekanbaru, an appropriate exercise is needed to improve agility. The population in this study is the 8-person Taekwondo Dojang Teratai Male Athlete of the Dojang Teratai Pekanbaru. In the research the sampling technique used was total sampling, the instrument used to collect data was the agility test with pree test and post test shuttle run. The data analysis technique used was the t test. The results showed that tcount was 7.124> 1.895 t table, then Ho was rejected and Ha was accepted, meaning that there was the effect of three corner drill practice on agility of athletes of male taekwondo Dojang Teratai Brimob Pekanbaru. When viewed from the difference in the average number of agility between the pree test and post test at 2 seconds, 13 seconds, this shows that the three corner drill practice on agility gives a better change of 14.53% compared to before being given training.Key Words: Three Corner Drill Exercise, Agility